The Integration of Local Species and Local Knowledge in Agroforestry Systems in Indonesia: A Systematic Mapping Study - Talantan, Puput; Saroinsong, Fabiola; Situmorang, Esra Nikita; Euis F. S. Pangemanan; Ratag, Semuel P. (Asia Pacific Journal of Interdisciplinary Studies, 2025)
Agroforestry systems are an innovative approach to land management that harmoniously integrates trees or forests with agricultural crops and livestock, creating a mutually supportive ecosystem. This approach not only increases land productivity but also contributes significantly to global food security, especially amid the challenges of climate change and environmental degradation. In addition, agroforestry plays an important role in biodiversity conservation by preserving natural habitats and preventing soil erosion, while providing economic benefits to farmers through crop diversification. Indonesia, as one of the world's megabiodiversity countries, has a wealth of local species, including various types of tropical trees, medicinal plants, and traditional food sources that have been integrated into agroforestry practices since ancient times. Species such as durian, petai, and various types of hardwood have become an integral part of local agricultural systems, which not only support ecological sustainability but also the culture of indigenous peoples. However, despite this great potential, knowledge about the use of local species in agroforestry in Indonesia is still limited, with many gaps in research that need to be identified to encourage more effective development. This study aims to map research trends, key study focuses, frequently used key species, and knowledge gaps related to the integration of local species in agroforestry systems in Indonesia. By conducting this mapping, this study is expected to reveal the temporal and geographical patterns of agroforestry research, identify under-explored endemic species, and highlight areas such as Java, Sumatra, and Kalimantan that have high potential but have not been fully researched. The SMS method applied involved a systematic and structured search of various leading scientific databases, such as Scopus, Web of Science, and Google Scholar, using specific keywords such as “agroforestry Indonesia,” “local species,” and “biodiversity conservation.” This process was followed by rigorous screening based on inclusion-exclusion criteria, which included publications in English and Indonesian from 2000 to the present, as well as a focus on relevant empirical studies or reviews. Data extraction was then conducted for quantitative analysis, such as publication frequency per year and geographical distribution, as well as qualitative analysis to identify key themes and knowledge gaps, such as the lack of studies on the impact of agroforestry on climate change or integration with modern technology. The mapping results from this study are expected to provide strategic guidance for researchers, policymakers, and agroforestry practitioners. These findings can encourage the development of more sustainable programs, such as the promotion of local species in organic certification schemes or the integration of agroforestry into national policies such as the National Biodiversity Action Plan. In addition, these results will help address knowledge gaps, such as the need for further research on the adaptation of local species to the threats of deforestation and urbanization, so that agroforestry can become an effective solution for food security and conservation in Indonesia.